How the COVID-19 Pandemic Affects Job Stress of Rural Teachers - Haizheng Li; Qinyi Liu; Mingyu Ma (Institute of Labor Economics (IZA), 2021)
This study investigates how the COVID-19 pandemic has affected teachers' job-specific stresses and their enthusiasm for the teaching occupation. We use unique data from China that cover the periods before and after the start of the pandemic and apply difference-in-differences type methods. We find that, among rural young teachers, the pandemic has caused higher teaching stress and career development stress and has reduced passion towards the teaching occupation. We investigate the working channels of the pandemic, including job-related activities and social network. After controlling for possible working channels, the COVID-19 pandemic still shows a strong direct impact on job sentiments.
Keywords: I18; J24; J28; 330; enthusiasm for occupation; job stress; pandemic; COVID-19